Ghrelin’s Effects on Proinflammatory Cytokine Mediated Apoptosis and Their Impact on β-Cell Functionality - Antonia Diaz-Ganete; Gloria Baena-Nieto; Isabel M. Lomas-Romero; Jose Francisco Lopez-Acosta; Irene Cozar-Castellano; Francisco Medina; Carmen Segundo; Alfonso M. Lechuga-Sancho (International Journal of Endocrinology)
Ghrelin is a peptidic hormone, which stimulates cell proliferation and inhibits apoptosis in several tissues, including pancreas. In preclinical stage of type 1 diabetes, proinflammatory cytokines generate a destructive environment for β-cells known as insulitis, which results in loss of β-cell mass and impaired insulin secretion, leading to diabetes. Our aim was to demonstrate that ghrelin could preserve β-cell viability, turnover rate, and insulin secretion acting as a counter balance of cytokines. In the present work we reproduced proinflammatory milieu found in insulitis stage by treating murine cell line INS-1E and rat islets with a cytokine cocktail including IL-1β, IFNγ, and TNFα and/or ghrelin. Several proteins involved in survival pathways (ERK 1/2 and Akt/PKB) and apoptosis (caspases and Bcl-2 protein family and endoplasmic reticulum stress markers) as well as insulin secretion were analyzed. Our results show that ghrelin alone has no remarkable effects on β-cells in basal conditions, but interestingly it activates cell survival pathways, downregulates apoptotic mediators and endoplasmic reticulum stress, and restores insulin secretion in response to glucose when beta-cells are cytokine-exposed. These data suggest a potential role of ghrelin in preventing or slowing down the transition from a preclinical to clinically established diabetes by ameliorating the effects of insulitis on β-cells.